PENERJEMAHAN FRASA VERBA BAHASA INGGRIS DALAM BUKU SOCIOLINGUISTICS: GOALS, APPROACHES AND PROBLEMS KARYA ROGER T. BELL KE DALAM BAHASA INDONESIA PADA BUKU SOSIOLINGUISTIK: SAJIAN, TUJUAN, PENDEKATAN DAN PROBLEM OLEH ABDUL SYUKUR IBRAHIM - Djoko Susilo (Universitas Muhammadiyah Ponorogo, 2018)
The research objectives are: firstly to describe verb phrase types used in ‘Sociolinguistics: Goals, Approaches and Problems’ of Roger T. Bell. Secondly, to describe the equivalent forms of English verb phrase in ‘Sociolinguistics: Goals, Approaches and Problems’ of Roger T. Bell and its translation in ‘Sosiolinguistik: Sajian, Tujuan, Pendekatan dan Problem’ by Abdul Syukur Ibrahim. Thirdly, it also describes the appropriateness of meaning of English verb phrase and its Indonesian equivalent forms in the two books mentioned before. This study used the qualitative descriptive method with purposive sampling. The categorization of data was taken from English verb phrase of Randolph Quirk’s et.al. The criterion of data selection was based on the research objections; proportion; and percentage of the total of English verb phrase of each type. The data consists of 52 English verb phrases in 52 sentences. This study used grammar approach in terms of its textual and contextual of verb phrase in the sentence both in English and in Indonesian. The study results showed that the use of English verb phrases have some variation as below: 25 % is perfective type; 5.77 % is progressive type; 38.46 % is passive; 9.61% is perfective progressive; 17.31 % is perfective passive; 3.85 % is progressive passive. The equivalent form of English verb phrase consists of two groups. There is not rank shift on the equivalent form of English verb phrase on one hand and there is rank shift on the other hand. In the former, 36.54 % of English verb phrase is translated into Indonesian verb phrase too. In the later, there are some rank shift variations. 1.92 % is English verb phrase level rank shift in Indonesian noun phrase; 48.08 % is English verb phrase shunt down into Indonesian verb; 9.61 % is English verb phrase shunt up into Indonesian embedded clause; and 3.45 % is ellipsis of English verb phrase into Indonesian equivalent. There are three groups of the meaning appropriateness in this study. For the first, 38.46 % of English verb phrase is appropriately translated into Indonesian equivalent. Secondly, 46.15 % English verb phrase is half appropriately translated into Indonesian equivalent. Thirdly, 15.39 % of English verb phrase is translated into Indonesian inappropriately cause of misinterpretation. From the two of the ellipsis of English verb phrase in Indonesian equivalent, 1.92 % is translated appropriately and 1.92 % is translated inappropriately due to misinterpretation. A translator should study the phenomena of non-passive of English verb phrase into Indonesian verb accurately so that the appropriateness of its meaning can be reached. In addition the translator has to study the meaning of verb + preposition structure accurately in Indonesia. This structure must be attended by students seriously because it is standard form in English but it is not in Indonesia. Thirdly, 1.72 % of English verb phrase is translated into Indonesian inappropriately cause of deviation and 15.39 % of English verb phrase is translated into Indonesian inappropriately cause of misinterpretation. Key Words: Translation, English Verb Phrase, Indonesian Verb Phrase